GCVS: COMPLETION OF THE 4th EDITION AND PROSPECTS OF COMPUTER DATABASE - Samus, N. N. (Одеські астрономічні публікації, 2017)
The work of Moscow astronomers according to the IAU behalf on compilation of the General Catalogue of Variable Stars is reviewed. The 4-th edition is nearly finished. The last, 5-th volume of the Catalogue will contain information on nearly 11000 variable stars in other galaxies. Special attention is paid to work on more precise coordinates of the variable stars contained, to the prospects of the automatization of the work and creation of the user-oriented computer database.